CUSTOMER PERCEPTION OF E-BANKING SERVICES AT PT. BANK RAKYAT INDONESIA - Zulkifli, Ahmad; Yani, Ahmad; Nilda, Elvi (Asian Journal of Islamic Economic Studies, 2024)
E-Banking services are banking services that can facilitate customers in obtaining information and conducting various types of banking transactions using electronic equipment. Each customer has a different picture of E-Banking services. The purpose of this study is to determine public perceptions about BRI E-Banking services and factors that influence people to use BRI E-Banking services. Researchers used qualitative methods with data collection techniques with interviews with 20 informants, as well as with documentation. Data analysis techniques through three flows, namely, data reduction, display data, and conclusions. From the results of the study, it is known that the existence of the BRI E-Banking service has a positive impact on the community, this is seen from the number of people who say that this service provides convenience in transacting both transfers, checking balances, or other transactions. The factors that influence people to use E-Banking services are ease of transactions, according to community needs, paying loan instalments, and making cash deposits.